2015
DOI: 10.3402/gha.v8.28405
|View full text |Cite
|
Sign up to set email alerts
|

‘Women think pregnancy management means obstetric ultrasound’: Vietnamese obstetricians’ views on the use of ultrasound during pregnancy

Abstract: ObjectiveTo explore Vietnamese obstetricians’ experiences and views on the role of obstetric ultrasound in clinical management of complicated pregnancy and in situations where maternal and fetal health interests conflict.DesignSeventeen obstetricians in northern Vietnam were interviewed as part of the CROss-Country Ultrasound Study (CROCUS) project in 2013. Data were analysed using qualitative content analysis.ResultsThe participants described ultrasound as a central tool in prenatal care, although they called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Another important finding of this study is that if these physicians’ perceptions are correct, women may perceive ultrasound as superior to other examinations during pregnancy. This result is comparable to our previous findings from Vietnam, where physicians felt that women at times perceived the obstetric ultrasound to be a ‘complete check’ of the pregnancy, resulting in less participation in clinical examinations in antenatal care . A tendency for both healthcare professionals and pregnant women to treat or regard ultrasound as superior to other fundamental examinations in pregnancy has also been reported in other studies from Vietnam , Botswana and Syria .…”
Section: Discussionmentioning
confidence: 98%
“…Another important finding of this study is that if these physicians’ perceptions are correct, women may perceive ultrasound as superior to other examinations during pregnancy. This result is comparable to our previous findings from Vietnam, where physicians felt that women at times perceived the obstetric ultrasound to be a ‘complete check’ of the pregnancy, resulting in less participation in clinical examinations in antenatal care . A tendency for both healthcare professionals and pregnant women to treat or regard ultrasound as superior to other fundamental examinations in pregnancy has also been reported in other studies from Vietnam , Botswana and Syria .…”
Section: Discussionmentioning
confidence: 98%
“…The study questionnaire was developed based on the results from the earlier qualitative studies performed in the CROCUS study 7 19–27. Sociodemographic characteristics, evaluation of self-reported skills in performing ultrasound, and questions about access to obstetric ultrasound and health professionals’ views on what may improve utilisation of ultrasound in Vietnam were included, among other items.…”
Section: Methodsmentioning
confidence: 99%
“…Low education, poverty, ethnic minority status6 and living in rural areas are factors associated with decreased access to reproductive health services 5. Ultrasound has become a central tool in ANC services in Vietnam 7. Currently the Ministry of Health in Vietnam recommends at least four ANC visits,8 in accordance with the previous recommendation by WHO 9.…”
Section: Introductionmentioning
confidence: 94%
“…Ultrasound is the most commonly used technic in the prenatal period, and it is more often used to determine the gender of the fetus . This study found that the number of ultrasound scans was lower for those who had a baby desired gender.…”
Section: Discussionmentioning
confidence: 83%
“…Ultrasound is the most commonly used technic in the prenatal period, and it is more often used to determine the gender of the fetus. 20,22 This study found that the number of ultrasound scans was lower for those who had a baby desired gender. The logistic regression analysis revealed that an increase in the number of ultrasound scans meant a 1.09 times greater risk factor associated with having a baby of the desired gender.…”
Section: Discussionmentioning
confidence: 85%